Badania archeologiczne dworu Zarembów w Kalinowej – siedziby jednego z najzamożniejszych rodów w średniowiecznej Polsce - Ginter, Artur (Acta Universitatis Lodziensis. Folia Archaeologica, 2019)
There is no possibility to talk about medieval Poland without Zaremba z Kalinowy family. Nowadays Kalinowa is a small village with gothic church and the XIX century looking palace surrounded by moat and lake from a north side. In XIV or beginning of XV century first manor house was build on the island. During our excavations in 2011 we discovered that in XV century new mansion was constructed on a mainland area. Inside there were beautiful late medieval tiled stoves, and rare artefacts (i.e. axe shaped badge) mostly known from large cities like Gdańsk or Kraków. In the XVII century Kalinowa was sold to Łubieńscy family. After that they build new palazzo in fortezza residence which was totally rebuilt in XVIII and XIX century.